2010
DOI: 10.1055/s-0030-1258508
|View full text |Cite
|
Sign up to set email alerts
|

Bis(benzotriazolyl)methanethione

Abstract: This feature focuses on a reagent chosen by a postgraduate, highlighting the uses and preparation of the reagent in current research Bis(benzotriazolyl)methanethioneCompiled by Archana Singh Archana Singh was born in Varanasi, Uttar Pradesh, India, in 1981. She obtained her B.Sc. from the P. G. College in 2003 and her M.Sc. in chemistry from the U. P. College, Varanasi, in 2005. She joined the research group of Dr. Vinod K. Tiwari at the Banaras Hindu University. Her current research is focused on the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In an attempt to advance the mechanochemistry of thioureas, which has been extensively investigated in our group, 12 we turned our attention to thiocarbamoyl benzotriazoles. Specifically, we explored the solid-state reactivity of bis(benzotriazolyl)methanethione (9) 13 as an easy-to-handle and much less toxic substitute for thiophosgene in the synthesis of isothiocyanates. 14 Surprisingly, thione 9 reacts with alkyl and aryl amines in different ways in solution; whereas stoichiometric reaction between 9 and an alkyl amine yields the corresponding alkyl thiocarbamoyl benzotriazole as a stable compound, aromatic derivatives proved to be unstable and too reactive in solution, directly affording the corresponding aromatic isothiocyanates (Figures 2a and 2b).…”
Section: Thiocarbamoyl Benzotriazoles: Taming the Reactive Intermediates By Mechanochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…In an attempt to advance the mechanochemistry of thioureas, which has been extensively investigated in our group, 12 we turned our attention to thiocarbamoyl benzotriazoles. Specifically, we explored the solid-state reactivity of bis(benzotriazolyl)methanethione (9) 13 as an easy-to-handle and much less toxic substitute for thiophosgene in the synthesis of isothiocyanates. 14 Surprisingly, thione 9 reacts with alkyl and aryl amines in different ways in solution; whereas stoichiometric reaction between 9 and an alkyl amine yields the corresponding alkyl thiocarbamoyl benzotriazole as a stable compound, aromatic derivatives proved to be unstable and too reactive in solution, directly affording the corresponding aromatic isothiocyanates (Figures 2a and 2b).…”
Section: Thiocarbamoyl Benzotriazoles: Taming the Reactive Intermediates By Mechanochemistrymentioning
confidence: 99%
“…14 Because these compounds readily decomposed in the solution environment, growing single crystals suitable for crystallographic analysis was not an option. For this reason, we resorted to structure determination directly from PXRD data obtained by high-intensity synchrotron radiation measurements, in combination with solid-state 13 C and 15 N NMR experiments. PXRD analyses of three derivatives indicated that the molecular structure indeed corresponded to those of thiocarbamoyl benzotriazoles.…”
Section: Syn Lettmentioning
confidence: 99%
See 2 more Smart Citations